Geological Characteristics of Unconventional Gas in Coal Measure of Upper Paleozoic Coal Measures in Ordos Basin, China (2016)
There are enormous resources of unconventional gas in coal measures in Ordos Basin. In order to study the geological characteristics of unconventional gas in coal Measures in Ordos Basin, we analyzed and summarized the results of previous studies. Analysis results are found that, the unconventional gas in coal measures is mainly developed in Upper Paleozoic in Eastern Ordos Basin, which including coalbed methane, shale gas and tight sandstone gas. The oil and gas show active in coal, shale and tight sandstone of Upper Paleozoic in Ordos Basin. Coalbed methane reservoir and shale gas reservoir in coal measures belong to “self-generation and self- preservation”, whereas the coal measures tight sandstone gas reservoir belongs to “allogenic and self-preservation”. The forming factors of the three different kinds of gasses reservoir are closely related and uniform. We have the concluded that it will be more scientific and reasonable that the geological reservoir-forming processes of three different kinds of unconventional gas of coal measures are studied as a whole in Ordos Basin, and at a later stage, the research on joint exploration and co-mining for the three types of gasses ought to be carried out.